Pelagibacterium limicola sp. nov., isolated from a soda alkali-saline soil - Wei, Wei; Xing, Kaiyan; Wang, Kaili; Hu, Xinyu; Zhang, Xin; Yang, Fan; Yang, Shujing; Cui, Henglin; Liu, Shenkui; Zhu, Lin (Archives of microbiology, 2021)
A Gram-staining negative, motile, non-spore-forming, rod-shaped bacterium, designated NAJP-14 T , was isolated from the alkali-saline soil in Heilongjiang, Northeast China. Phylogenetic analysis based on 16S rRNA gene sequencing illustrated that strain NAJP-14 T was a member of the genus Pelagibacterium , and shared 94.6–96.6% sequence identities to species from the genus Pelagibacterium. Strain NAJP-14 T grew at 20–45 °C (optimum, 30 °C), pH 7.0–10.0 (optimum, pH 8.0) and in the presence of up to 5% w/v NaCl. The menaquinone was determined to be Q (10). The major fatty acids were identified as C 18:1 w6c (38.7%), C 16:0 (16.2%) and C 19:0 cyclo w8c (13.9%). The G + C content of the genomic DNA was 61.2%. Out of the 3442 predicted genes, 3391 were protein-coding genes and 51 were ncRNA. Digital DNA–DNA hybridization (dDDH) estimation and average nucleotide identity (ANI) of the strain NAJP-14 T and the type strains of related species in the same family ranged between 17.9 and 21.8% and between 61.4 and 78.7%, respectively. Based on these data, it is concluded that strain NAJP-14 T possesses sufficient characteristics to differentiate it from all recognized Pelagibacterium species, and should be considered as a novel species for which the name Pelagibacterium limicola sp. nov. is proposed. The type strain is NAJP-14 T (= CGMCC 1.16631 T , = JCM 33746 T ).